2017
DOI: 10.1007/s00401-017-1685-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies four novel loci associated with Alzheimer’s endophenotypes and disease modifiers

Abstract: More than 20 genetic loci have been associated with risk for Alzheimer’s disease (AD), but reported genome-wide significant loci do not account for all the estimated heritability and provide little information about underlying biological mechanisms. Genetic studies using intermediate quantitative traits such as biomarkers, or endophenotypes, benefit from increased statistical power to identify variants that may not pass the stringent multiple test correction in case–control studies. Endophenotypes also contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
237
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 206 publications
(265 citation statements)
references
References 85 publications
27
237
1
Order By: Relevance
“…We utilized data from a GWAS for CSF biomarkers published by Deming and colleagues [20]. The original data for this study was collected from 3,146 individuals across nine cohort studies, including ADNI.…”
Section: Polygenic Risk Score Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized data from a GWAS for CSF biomarkers published by Deming and colleagues [20]. The original data for this study was collected from 3,146 individuals across nine cohort studies, including ADNI.…”
Section: Polygenic Risk Score Calculationmentioning
confidence: 99%
“…Additionally, the National Institute on Aging and Alzheimer's Association released a research framework for AD in which the pathological accumulation of amyloid plaques (A), neurofibrillary tangles composed of tau (T), and neurodegeneration (N) are recommended to be included in diagnostic categories of AD used for research [19]. While this A/T/N framework has emerged in studies of preclinical disease, it has not been integrated into PRS for AD despite the availability of GWAS summary statistics for autopsy and in vivo measures of A/T/N [20,21]. Indeed, a previous study suggested that shared genetic drivers for hippocampal volume (a marker of neurodegeneration) and AD may exist [22].…”
Section: Introductionmentioning
confidence: 99%
“…ApoE has been shown to directly bind tau in vitro 6 , and neuronal expression of human ApoE in vivo results in tau hyperphosphorylation (E4>E3) 7 . Recent GWAS studies show a strong and significant association of APOE with CSF tau and p-tau after correcting for the effect of APOE on Aβ42 levels 8 . In frontotemporal dementia (FTD) patients, a large percentage of whom have tauopathy, ε4 allele frequency was reported to be significantly elevated 9,10 , and ε4 carriers have greater atrophy in affected brain regions 11 as well as exacerbated behavioral deficits 12 .…”
mentioning
confidence: 99%
“…Rs476155 was identified as a susceptibility locus for low HDL-cholesterol levels, a risk factor for coronary artery disease in ethnic Arabs [84]. A significant association was also found between the GLIS3 SNP, rs514716, and elevated levels of cerebrospinal fluid (CSF) tau and phosphorylated tau (ptau 181 ), established biomarkers for AD [85, 86]. No significant correlation was found between T2D-associated GLIS3 SNP, rs10814916, and risk of Parkinson’s or Alzheimer’s disease (AD) [87].…”
Section: Genetic Alterations In Human Glis1–3mentioning
confidence: 99%
“…GLIS1 variants have been reported to be a risk factor for several neural pathologies. The intergenic SNP, rs185031519, near the GLIS1 locus was found to be associated with lower cerebrospinal fluid (CSF) amyloid-beta1–42 (Aβ 42 ) levels and higher tau and phosphorylated tau (ptau 181 ) levels [86]. Lower CSF Aβ 42 levels and higher tau and ptau 181 correlate with the number of neurofibrillary tangles and plaque load and are well-established AD endophenotypes.…”
Section: Genetic Alterations In Human Glis1–3mentioning
confidence: 99%